Rethinking the Guardianship of Refugee Children after the Malaysian Solution - Crock, Mary; Kenny, Mary (Lawbook Co., 2012)
The arrival of children seeking asylum in Australia without a parent or guardian continues to pose challenges for the Australian government’s legislative and policy framework. The central problem is the potential for conflict between the Minister for Immigration’s responsibility as guardian under the Immigration (Guardianship of Children) (IGOC) Act 1946 (Cth) (‘IGOC Act’) and the Minister’s roles under the Migration Act 1958 (Cth) (‘Migration Act’). The rise in the number of unaccompanied children presenting as irregular maritime arrivals has led to various attempts to challenge Ministerial interpretations of the IGOC Act. The authors show that successive governments have fought hard to deny much or any content to the Ministerial role of guardian. They examine a series of cases leading up to the High Court ruling which invalidated Australia’s ‘Arrangement’ to transfer asylum seekers, including unaccompanied minors, to Malaysia. Although a clear departure from earlier jurisprudence, they argue that the ruling in Plaintiff M70/2011 and Plaintiff M106/2011 v Minister for Immigration and Citizenship should not have surprised or confounded the government as much as it did. The case provides an important object lesson in doctrinal exegesis. Rulings made at a point in time rendered fraught by war, terrorist attacks or other acute events cannot be expected again when a matter is re-litigated a decade later and in a period of relative calm. The authors argue that the current impasse in relation to offshore processing of asylum seekers presents an opportunity to reconsider Australia’s approach to this vulnerable group: children seeking asylum alone.